Gender Representation in EFL Textbooks for Elementary Schools: A Content Analysis - Winda Khoirun Nisak; Furaidah Furaidah; Gunadi Harry Sulistyo (Graduate School of Universitas Negeri Malang, 2020)
Abstract: This research is a study of assessing the representation of gender in elementary school textbooks used by an international curriculum that is widely used in 160 countries throughout the world. The content analysis used to lead the representation of the male and female on the textbooks. The findings of this study indicate that the gender representation formed in the textbook shows the existence of gender equality which is reflected in the balanced emergence of male and female characters that appear in textbooks, the prevalence of the professional picture of men and women and the balance of household activities reflected in the textbook.Abstrak: Penelitian ini merupakan penelitian mengenai representasi gender di buku teks siswa sekolah dasar yang dipakai oleh kurikulum internasional yang tersebar luas di 160 negara di seluruh dunia. Konten analisis dipakai untuk melihat representasi dalam buku. Temuan dari penelitian ini menunjukkan bahwa konstruksi gender yang terbentuk dalam buku teks tersebut menunjukkan adanya kesetaraan gender yang tercermin dari berimbangnya kemunculan karakter laki laki dan perempuan yang muncul dalam buku teks, meratanya gambaran profesi laki-laki dan perempuan serta berimbangnya kegiatan rumah tangga yang tercermin dalam buku teks.